Evaluation of the quality of the doctor-patient relationship in the Northeast of Portugal - Gomes da Silva, Joana (2024)
Introduction: The family doctor develops a person-centered approach, oriented toward the individual, the family, and the community in which he is inserted, with empathy being the major key to this relationship. Objectives: Understand the doctor-patient relationship in the context of primary health care (PHC) in the Northeast of Portugal. Methods: A descriptive study was carried out with a sample of PHC. Demographic data (biological sex-binary classification, age, county of residence, and education), questions about the perception of PHC, and the application of the Jefferson Empathy Scale (JSPPPE-VP) were collected through an online platform with the dissemination of information through social media and physical format in PHC of the Unidade Local de Saúde do Nordeste. Descriptive statistical analysis was performed using the IBM SPSS® Statistics software. Results: The sample consisted of 584 individuals (median age: 45 years old), mostly women (67.47%), with an undergraduate level of education (57.71%). Most people (75.51%) say that their family doctor is the first person that they turn to when they have a health problem because they believe he has the necessary skills to better manage their health problems (69.52%). In terms of accessibility, 61.30% and 60.96% respectively consider that it is easy to get an appointment and to clarify specific doubts. Of the respondents, 22.95% did not agree with the average duration of consultations (20 minutes), preferring 30 minutes. When the JSPPE-VP was applied, approximately 50.00% of the respondents indicated that they strongly or completely agreed with all the items evaluated. Conclusions: The sample obtained showed overall satisfaction with the provision, accessibility, and quality of services, as well as the duration of the consultation. It can also be concluded that there is a high level of satisfaction with the empathy of the family doctor.